Caregiver Training in Mindfulness-Based Positive Behavior Supports (MBPBS): Effects on Caregivers and Adults with Intellectual and Developmental Disabilities - Singh, Nirbhay N.; Lancioni, Giulio E.; Karazsia, Bryan T.; Myers, Rachel E. (Frontiers in Psychology, 2016)
Caregivers often manage the aggressive behavior of individuals with intellectual and developmental disabilities that reside in community group homes. Sometimes this results in adverse outcomes for both the caregivers and the care recipients. We provided a 7-day intensive Mindfulness-Based Positive Behavior Support (MBPBS) training to caregivers from community group homes and assessed the outcomes in terms of caregiver variables, individuals’ behaviors, and an administrative outcome. When compared to pre-MBPBS training, the training resulted in the caregivers using significantly less physical restraints, and staff stress and staff turnover were considerably reduced. The frequency of injury to caregivers and peers caused by the individuals was significantly reduced. A benefit-cost analysis showed substantial financial savings due to staff participation in the MBPBS program. This study provides further proof of concept for the effectiveness of MBPBS training for caregivers, and strengthens the call for training staff in mindfulness meditation.